Effect of breathing exercises on oxidative stress biomarkers in humans: A systematic review and meta-analysis - Li, Ting-ting; Wang, Hong-ying; Zhang, Hui; Zhang, Ping-ping; Zhang, Ming-chen; Feng, Hai-yang; Duan, Xiao-yong; Liu, Wen-bo; Wang, Xiao-wen; Sun, Zhong-guang (Frontiers in Medicine, 2023)
Background: Breathing exercises improve oxidative stress in healthy young adults and patients with diabetes, hypertension, and chronic obstructive pulmonary disease. Breathing exercises improve oxidative stress in healthy young adults and patients with diabetes, hypertension, and chronic obstructive pulmonary disease. Furthermore, the mechanism of respiratory intervention is controversial. Therefore, in this meta-analysis, we aimed to systematically evaluate the effects of breathing exercises on oxidative stress biomarkers in humans and provide evidence for the clinical application of breathing exercises. Methods: The Embase, PubMed, Cochrane Library, Web of Science, CNKI, and WANFANG databases were searched for studies about the effects of breathing exercises on human oxidative stress levels, with no restraints regarding time, race, or language. The experimental group included various breathing exercises, and the outcome index included malondialdehyde, superoxide dismutase, and glutathione, nitric oxide, vitamin C, or total antioxidant capacity levels from a randomized controlled trial. Data were extracted by more than two authors and reviewed by one author. Results: Ten studies were included from five countries. Data from patients with no disease, chronic obstructive pulmonary disease, hypertension, or diabetes were included. Participants who performed breathing exercises had greater changes in the included biomarkers than those who did not, suggesting that these biomarkers can be used to evaluate oxidative stress after respiratory interventions. Conclusions: Breathing exercises increased SOD and GSH activities and decreased MDA content.